THE DANGERS OF GODFATHERISM IN ELECTORAL PROCESS: THE NIGERIAN EXPERIENCE - FAVOUR EKE, GABRIEL; SADO OSAYANDE OSAGHAE, FELIX (IJRDO - Journal of Social Science and Humanities Research, 2016)
The paper discusses the destructive trends in Nigerian political Phenomenon known as Godfatherism. It states that this was the reason why Nigeria after fifty years ofindependence, has not made any serious impact in its political development, while it continues to blame the colonial masters for its problems. The paper was of theopinion that this is the phenomenon in which wealthy and powerful individuals in the society multiply corruption by installing their protégé in office. By this method,the candidates no longer depend on their popularity with the people, but by the whims and caprices of the Godfathers. The paper explains the danger of this method,in that people no longer have trust in our electoral system because violence, intimidation and subversion of the rule of law become the order of the day, hencethe dearth of development becomes the resultant effect. Also, the oath taking by prospective candidates in a shrine before their Godfathers as a pre-requisite foracceptance and a guarantee to fulfilling their agreement is also presented here with exemplifications. The paper concludes, interalia the holistic reconfiguration of thetotal apparatus of the Nigerian state; the phenomenon called Godfatherism be abrogated in the Nigerian political life and ultimately, the nation’s electoral lawsshould be strengthened and offenders be allowed to face the whole wrought of the law.